Stumbling Into Adulthood: Learning From Depression While Growing Up. (July 2020) - Grob, Rachel; Schlesinger, Mark; Wise, Meg; Pandhi, Nancy
Depression manifests in distinct ways across the life course. Recent research emphasizes how depression impedes development during emerging adulthood. However, our study—based on 40 interviews with emerging adults from multiple regions in the United States, analyzed following grounded theory—suggests a more complex narrative. Increasing experience with cycles of depression can also catalyze (a) mature perspectives and coping mechanisms that protect against depression's lowest lows; (b) deeper self-knowledge and direction, which in turn promoted a coherent personal identity; and (c) emergence of a life purpose, which fostered attainment of adult roles, skill development, greater life satisfaction, and enriched identity. Our synthesis reveals how depression during emerging adulthood can function at once as toxin, potential antidote, and nutritional supplement fostering healthy development. Our central finding that young adults adapt to rather than recover from depression can also enrich resilience theory, and inform both social discourse and clinical practice.